Virtual environments and the person with hearing impairment: Working the process of teaching and education during globalization (Research, Society and Development, 2021)
Introduction: Historically, people with hearing impairment have always had their socialization spaces restricted. Information and Communication Technologies are becoming valuable support tools to overcome inequalities and contribute to social inclusion. Objective: Describe how virtual environments help people with hearing impairments in terms of education, socialization and globalization. Methodology: The work is an exploratory study, through a bibliographical research. Results and Discussion: It was found that virtual environments are of paramount importance in formal education, as they improve the learning of people with addictive disabilities, especially with the use of videos. Social networks form a great environment capable of disseminating and globalizing culture for people with hearing impairments. Conclusion: The use of virtual environments is significantly important to explore the teaching, learning and socialization of people with hearing impairment, however, the site interfaces are still poorly planned, with the use of written oral language, making it difficult to use these environments. Thus, our article guides that for a more effective teaching, such tools are improved with a focus on learning and socialization of people with hearing impairment.